Women and Wealth: Financial Propinquity to Business Success - Nikunj Aggarwal; Harjit Singh (Australasian Accounting, Business and Finance Journal, 2019)
Around the globe, women’s income and wealth are increasing as never before. Prevailing economic, demographic, and technological changes are growing women’s financial strength and independence. Be it finance, marketing, supply chain or ICT based industry, women have made incredible strides, both at professional and social fronts, particularly in the two decades. Today they are better educated, well placed and have greater accountability in the corporate world and are frontrunners in many professions. Consequently, women, particularly in developing countries like India and China have become economic powerhouses. They not only significantly contribute to GDP but also are becoming a substantial untapped market for the wealth management industry. In this context, this study is an attempt to discuss the much talked about, but less understood, issue of women’s wealth management in the Indian context. The study is intended to explore financial planning awareness among working women and their attitude towards wealth management. The findings will help wealth managers and financial planners to develop a deeper understanding of female investors’ goals and priorities, investment patterns of the working women and to gain insight into gender specific investment behaviour of Indian investors.
Keywords: Wealth Management; Women; India; Gender; Financial Literacy; Financial Security; Investment Planning; Financial Awareness.